The video game as agencement and the image of new gaming experiences: the work of indie video game developers. Issue 6 (2nd November 2021) - Styhre, Alexander; Remneland-Wikhamn, Björn
ABSTRACT : The growth of the global video game industry has resulted in an inflow of new entrants who aspire to create novel video games and preferably new video game genres. From an empiricist perspective presented by Gilles Deleuze, a video game is an agencement that materialize on the basis of the relations between the elements included in the game (e.g. computer code, game design ideas, the narrative structure of the game, interface design, etc.). A study of indie video game developers examines how the video game as agencement is composed of technical and narrative elements, and how the subject-formation process of the developer is bound up with the creation of video games. That is, indie video game developers are part of the creative work to develop new digital artefacts that per se are relational and composite in nature, as premised by the concept of agencement.